2015
DOI: 10.1111/jsm.12966
|View full text |Cite
|
Sign up to set email alerts
|

Development and Initial Validation of the PROMIS® Sexual Function and Satisfaction Measures Version 2.0

Abstract: Introduction The Patient-Reported Outcomes Measurement Information System (PROMIS)® Sexual Function and Satisfaction measure (SexFS) version 1.0 was developed with cancer populations. There is a need to expand the SexFS and provide evidence of its validity in diverse populations. Aim The aim of this study was to describe the development of the SexFS v2.0 and present preliminary evidence for its validity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
141
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 150 publications
(148 citation statements)
references
References 22 publications
4
141
3
Order By: Relevance
“…The responses were summed for a total score with a possible range of 10–49 (https://assessmentcenter.net/Manuals.aspx). The Vaginal Discomfort scale has been shown to have good convergent validity with the Pain subscale of the Female Sexual Function Index (FSFI; r = − .85) (Weinfurt et al, 2015) and demonstrated good reliability (alpha =0.88) in the current study.…”
Section: Methodsmentioning
confidence: 59%
“…The responses were summed for a total score with a possible range of 10–49 (https://assessmentcenter.net/Manuals.aspx). The Vaginal Discomfort scale has been shown to have good convergent validity with the Pain subscale of the Female Sexual Function Index (FSFI; r = − .85) (Weinfurt et al, 2015) and demonstrated good reliability (alpha =0.88) in the current study.…”
Section: Methodsmentioning
confidence: 59%
“…The SVQ went through extensive qualitative and quantitative testing with more than 350 Danish women with gynecologic cancer, as well as input from oncology clinicians. Similar to the iterative process used to develop the SVQ, the PROMIS SexFS was developed with more than 800 U.S. male and female cancer patients during active treatment or follow-up care for multiple cancer sites (Flynn, et al, 2013; Weinfurt, et al, in press). Features that set the PROMIS SexFS apart from the other identified measures include the use of item response theory (IRT) to estimate latent sexual function constructs, to calculate differential item functioning, and to assess measurement invariance for each domain.…”
Section: Discussionmentioning
confidence: 99%
“…Professional focus group moderators of the same gender as participants led discussions by following a semistructured guide developed by a multidisciplinary domain committee. The guide was based on 1) a previous guide used in focus groups with patients with cancer, 24 2) literature review, 3) input from telephone discussions with a convenience sample of physicians, advanced practice providers, and nurses (15 providers in 6 discussions) who specialized in treating patients with heart failure, diabetes, anxiety, or depression, or sexual dysfunction, 18 and 4) input from a telephone discussion with a convenience sample of experts in sex research and measurement of sexual function (2 experts).…”
Section: Methodsmentioning
confidence: 99%
“…18 Thus, the original analysis was conducted with the goal of refining item content for a self-report measure. The current research presents a new, more detailed analysis than was conducted during the original analysis, focused on elucidating the meaning of key terms to the participants in the focus groups.…”
Section: Methodsmentioning
confidence: 99%